Ответы и объяснения

2013-02-12T22:03:31+04:00

5x^2 + 14x - 3 = 0

D = b^2 - 4ac = 14^2 - 4*1*(-3) = 196 + 12 = 208

VD = V(16*13) = 4V13

 

           -14 + 4V13           -14 + 4V13

x1 = -------------------- = -------------------

                 2*5                         10

 

            -14 - 4V13            -14 - 4V13

x2 = ------------------- = --------------------

                 2*5                            10

 

 

 

 

5x^2 + 3x - 2 = 0

D = b^2 - 4ac = 3^2 - 4*5*(-2) = 9 + 40 = 49

VD = V49 = 7

x1 = (-3+7)/2*5 = 4/10 = 2/5

x2 = (-3-7)/2*5 = -10/10 = -1